DUNIA BATIN JAWA: Aksara Jawa Sebagai Filosofi dalam Memahami Konsep Ketuhanan - Fatkur Rohman Nur Awalin (IAIN Tulungagung, 2017)
The inner world of Java applied into Javanese script is a philosophy of understanding divinity. The Javanese script Hanacaraka Datasawala Padhajayanya Magabathanga is not used as a medium of writing by Javanese. Javanese script is used as a medium in understanding divinity. Each alphabet Javanese have a meaning related to divinity. One is Ha-na-ca-ra-ka which means there is a messenger, that messenger of life, such as breathing obliged to unite the soul with the human body. It means there are those who trust, some are trusted and some are believed to work, the three elements are God, man and human duty (as his creation). Apart from the elements script story of the formation of Javanese script from the mythical path with figures Aji Saka, Dewa Cengkar, Dora, Sembodo, Dedugo and Prayoga also have the meaning of philosophy. All of them lead to the knowledge of the Lord. Manhas a relationship with God.